Thallium concentration and thallium isotope composition of lateritic terrains. (15th October 2018) - Howarth, S.; Prytulak, J.; Little, S.H.; Hammond, S.J.; Widdowson, M.
Abstract: Continental weathering plays a key role in modifying the geochemical budget of terrestrial reservoirs. Laterites are the products of extreme sub-aerial continental weathering. This study presents the first investigation of thallium (Tl) abundances and stable isotopic compositions of lateritic terrains. Two laterite profiles from India of differing protolith and age are studied. Thallium concentrations range between 7 and 244 ng/g for a basalt-based lateritic profile and 37–652 ng/g within a greywacke lateritic profile. The average Tl stable isotope composition of the two profiles is similar to many typical igneous materials, however, the intense tropical weathering causes a small but resolvable fractionation of Tl stable isotopes towards heavy values in the residual soils. The profiles are dominated by significant positive isotope excursions (reported as ε 205 Tl relative to standard NBS997) of +3.5 ± 0.5 2sd and +6.2 ± 0.5 2sd at the inferred palaeowater tables within both laterite profiles. These signatures likely reflect combined changes in redox state and mineralogy. Extensive mineral dissolution under through-flowing fluids alongside the formation of new phases such as phyllosilicates and Mn- and Fe-oxides and hydroxides likely account for some of the Tl mobilisation, sorption and coprecipitation. In the case of laterites, the formation of the new phases and role of surface sorption likely contribute to stable Tl isotope fractionation. The identification of strong isotope excursions at inferred palaeowater tables encourages future research to determine specific mineral phases that may drive significant fractionation of Tl stable isotopes. This study showcases the magnitude of natural variation possible in terrestrial soils. Such information is key to the nascent application of Tl isotope compositions as tracers of anthropogenic pollution.